Analysis of soil in the area of ​​the airport Kyiv - Маджд, С.М.; Михалєвська, Т.В.; Франчук, Г.М. (Proceedings of National Aviation University (archive), 2007)
The technogenic pressure imposed on the soils in the airport vicinity is discussed. The analysis of the database on the soils condition was carried out using mathematical models. The multitude correlation model was built for the purpose of environmental factor indexes assessment.